Brazil : Evaluating the Macroeconomic and Distributional Impacts of Lowering Transportation Costs - World Bank (Washington, DC, 2012)
This report is designed to provide policymakers with estimates of the likely outcomes of an array of potential changes in transportation sector policy. To this end, the report uses a variety of economy-wide models to simulate alternative cost reductions and efficiency improvements. A detailed discussion of the various policies that may yield efficiency gains and cost reductions, as well as the specifics of their implementation, is beyond the scope of the report. The report is structured to move from a general description of Brazil's transportation sector to more specific analyses and simulations of individual and concerted changes. The first chapter sets the stage by providing a summary discussion of Brazil's transportation sector that includes both an overview of its historical development and a look at the recent evolution of government policies. In the second chapter, the fiscal and economic effects of shifts in public investment between alternative and competing transportation modes (roads, railroads, and waterways) are simulated using a fixed-price input-output model. The report's third chapter uses a computable general equilibrium (CGE) model to analyze the effects of cost reductions in land transportation on macroeconomic variables and income distribution. The fourth chapter uses a multiregional CGE model to simulate the effects of port efficiency improvements on regional economic development (including short- and long-term growth, employment, and welfare). The fifth chapter uses a similar model to analyze the national and state-level impacts of two federal highway projects in the state of Minas Gerais in terms of economic growth, regional inequalities, employment, and poverty. The last chapter summarizes the findings and provides conclusions and recommendations.